Penyuluhan dan Edukasi Kesehatan Serta Menumbuhkan Minat Baca dan Belajar pada Tahapan Awal Pembelajaran Tatap Muka di Era Pandemi - Saputra Saputra; Jasmi Indra; Kurniawan Lase; Yudi Catur Prakoso; Diny Megawaty Meraye (Abdimisi, 2020)
One way to deal with the COVID-19 pandemic is to increase understanding regarding the prevention and handling of COVID-19, both at the individual and community levels. This pandemic has sparked our desire to carry out counselling and education activities as well as practices on concrete ways to maintain health. It is hoped that through this activity, students, especially the Darussalam Terpadu Junior High School, are able to practice healthy living habits in the context of preventing the spread of COVID-19 every day at school or wherever they visit. The results of this activity are able to improve healthy living habits wherever they are without being coerced by anyone. Developing an interest in reading must be done to school students because with reading interest students have broad insight and enrich knowledge and understanding as well as hone creativity. . The purpose of this Community Service (PKM) is to provide an understanding of the importance of maintaining a healthy lifestyle and concrete ways to maintain health during the pandemic during face-to-face learning at school, including maintaining distance, wearing masks, washing hands using liquid soap. , and using a hand sanitizer and fostering interest in reading by making interesting presentations and distributing interesting books to read so that the students of SMP Terpadu Darussalam have broad insight and train focus and concentration in learning.